Advances in the Integration of Technology and the Built Environment Select Proceeding of Architecture Across Boundaries 2024 - Han, Jiawen; Lombardi, Davide; Cece, Alessandro; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2025)
This open access book will be a compilation of selected papers from the 2nd International Conference on Architecture Across Boundaries (AAB2024). The work focuses on novel integration of technology into the built environment in the areas of space syntax, digital fabrication, computational design, professional models, eco-system and urban morphology domains. The content makes valuable contributions to academic researchers and educators in the university and practitioners in the industry, who have been working in or with a particular awareness of the different types of boundaries, including technological, cultural and physical boundaries in the research on built environments. This book will work as a good reference for academics and professionals conducting interdisciplinary research in an effort to understand and achieve a better hybrid environment.
Computational design and digital fabrication without boundaries -- Systemic approaches to architectural design -- Urban prosthetics across technology and morphology -- Architectural education and professional practice across contexts -- New Typologies of Hybrid Spaces.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Architecture; Buildings -- Design and construction; Computer-aided engineering; Architecture; Building Construction and Design; Computer-Aided Engineering (CAD, CAE) and Design